The Effect of Cognitive Behavioral Therapy (CBT) on Low Self-Esteem Among Students - Salsabila, Sifa; Syafril, Syafrimen (International Journal of Multidisciplinary Research of Higher Education, 2026)
For students, low self-esteem is a psychological issue that impacts their academic, emotional, and social development. Research has found that Cognitive Behavioral Therapy (CBT) is one of the most widely used counseling methods to address this issue. This study aims to analyze the effectiveness of Cognitive Behavioral Therapy (CBT) in improving students’ self-esteem and to identify the factors contributing to its success. This research employs a Systematic Literature Review (SLR) method using a structured approach that includes the identification, screening, eligibility, and inclusion stages. This procedure was used to systematically identify, select, and analyze 1,087 articles indexed in Sinta and Scopus published between 2016 and 2025. The results indicate that Cognitive Behavioral Therapy (CBT) is effective in enhancing students’ self-esteem through cognitive restructuring and anxiety reduction, supported by individual and group interventions as well as enabling factors such as counselor competence and student engagement. These findings suggest that Cognitive Behavioral Therapy (CBT) can be used by school counselors and guidance counselors as an effective intervention to improve students’ self-esteem. Furthermore, this study encourages the development of a more systematic, adaptive, and technology-integrated implementation of CBT in future counseling services.